A Covid deixa sequelas: A destruiç\~ao do estoque de capital das micro e pequenas empresas como consequência da pandemia de Covid-19 - Mauro Oddo Nogueira; Rafael De Farias Costa Moreira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The covid-19 pandemic has been devastating for small businesses, being responsible for an abrupt fall in demand, interruption of economic activities, and, in many cases, bankruptcy of numerous enterprises. Data from Brazilian Institute of Geography and Statistics (IBGE) indicate that, until June 2020, 716,372 companies had gone bankrupt; 99.8 % of which were small-sized. Such an impact implied a significant loss of capital stock. Using IBGE data, this paper presents an original estimate of the total capital of stock of Brazilian companies by size and sector. We use this data and the results from IBGE's survey "Enterprise's Pulse - Impact of covid-19 on companies" and conservatively assess that until June 2020 micro and small businesses had lost capital estimated to be in the range from 9.1 to 24.1 (in R of December 2020), with the retail and services sectors being the most impacted. Considering the amount of capital stock lost and the average annual growth of capital formation in small businesses from 2014 and 2018, if there are no government intervention to respond to this situation, it should take between 1 and 3 years to replenish it fully. If we had considered all businesses that have gone bankrupt since June 2020 (last available data), the 14 million individual micro entrepreneurs who were not included in the data, the millions of informal enterprises, and the loss of intangible capital, it is certain that the total capital stock lost amount to more than R 50 billion (in 2022 values). The estimates presented aim to provide data that could be used to support the design of public policies focused in rebuilding the capital stock lost, as well as policies centered in facilitating financing to small businesses.
Keywords: C13; D22; D24; E22; H12; H54; O16; 330; micro and small business; capital stock; covid-19